1985
DOI: 10.1177/00220345850640020201
|View full text |Cite
|
Sign up to set email alerts
|

Glycylprolyl Dipeptidylaminopeptidase from Bacteroides gingivalis

Abstract: Dipeptidyl aminopeptidase activity was found in the culture medium of Bacteroides gingivalis 381. The enzyme, hydrolyzing glycylprolyl-4-methylcoumaryl-7-amide, was purified 750-fold from culture medium by ammonium sulfate precipitation, Sephadex G-200 gel filtration, and DEAE Bio Gel A column chromatography. The molecular weight, determined by gel filtration, was approximately 160,000. The isoelectric point of the enzyme, estimated by isoelectric focusing using polyacrylamide disk gel electrophoresis, was abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 23 publications
6
60
0
Order By: Relevance
“…Cleavage site a gelatinolytic activity, a pH optimum around 6.5, and an activity which is insensitive to treatment with 20 mM SDS, differs in all parameters from DPPIV (17) and therefore cannot be the enzyme described in this report. A second peptidase with a molecular mass of approximately 160 kDa was partially purified and not fully characterized (1). Only the surface-located 80-kDa protease described by Barua et al (6) has characteristics in common with DPPIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleavage site a gelatinolytic activity, a pH optimum around 6.5, and an activity which is insensitive to treatment with 20 mM SDS, differs in all parameters from DPPIV (17) and therefore cannot be the enzyme described in this report. A second peptidase with a molecular mass of approximately 160 kDa was partially purified and not fully characterized (1). Only the surface-located 80-kDa protease described by Barua et al (6) has characteristics in common with DPPIV.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, glycyl-prolyl peptidase, which recently has been found to be a homologue of human prolyl dipeptidyl peptidase IV (DPPIV) (CD26) (26), may have an important function because of the ability of P. gingivalis to thrive on dipeptides as the sole source of carbon (38). This serine protease was previously partially purified and characterized, but conflicting data on its molecular mass and biochemical properties were reported (1,6,16). In addition, the detection of three DPPIV-related genes expressed in P. gingivalis (3) suggests that a rigorous purification of this enzyme(s) is necessary to ensure the separation from other related peptidases.…”
mentioning
confidence: 99%
“…The S. suis DPP IV may also contribute to tissue destruction and systemic bacterial dissemination. Indeed, Abiko et al (1) reported that the DPP IV of P. gingivalis can further degrade peptides from partially digested type I collagen. The dipeptides produced may also promote bacterial growth.…”
Section: S Suismentioning
confidence: 99%
“…In P. gingivalis PTP-A, as well as in dipeptidyl peptidase IV (19), all activities are cell surface associated, and it is conceivable that the enzymes are membrane anchored through putative signal sequences, which are not cleaved but remain as a membrane-spanning domain similar to other members of the prolyl oligopeptidase family (32). However, a significant portion of the purified PTP-A has a truncated amino terminus, apparently attributable to cleavage by Lys-specific proteinase and likely to be an artifact that has occurred during the purification procedure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an enzyme referred to as glycylprolyl peptidase (dipeptidyl peptidase IV) was found to be associated with bacterial surfaces (16), and two molecular mass forms of this peptidase have been described (17,18). This enzyme(s) has also been shown to possess the ability to hydrolyze partially degraded type I collagen, releasing the Gly-Pro dipeptide, and it was suggested that, in collaboration with collagenase, dipeptidyl peptidase IV may contribute to the destruction of the periodontal ligament (19). In addition to this potential pathological function, glycylprolyl peptidase may also play a vital role in providing P. gingivalis with dipeptides, which can be transported inside the cell and serve as a source of carbon, nitrogen, and energy for this asaccharolytic organism.…”
mentioning
confidence: 99%